(untitled) (Third Sector Social Economic Review, 2023)
In this research, the effect of technological unemployment anxiety on organizational cynicism has been examined. To collect data questionnaires were utilized. Principal component analysis was employed to ensure the validity of the scales. Cronbach alpha values were calculated to evaluate reliability. The hypotheses were tested by using structural equation modelling method. As the result of the analyses performed, out of nine hypotheses, five of them were supported. It has been empirically proven that Technological Unemployment Anxiety has positive effect on Organizational Cynicism. According to the findings of the analyses, lack of technical skill does not have a direct effect on any dimensions of organizational cynicism; incremental technological improvements have a direct effect on all dimension’s organizational cynicism; technological disruption has a direct effect on affective and cognitive dimensions of organizational cynicism. Although the relationship between organizational cynicism and various theoretical concepts are subjects that have been researched for years, this original research adds to the literature by investigating how organizational cynicism is affected within the framework of technological unemployment anxiety. The study’s findings demonstrated the need for additional research to diminish the negative consequences of technological unemployment anxiety.